A Design: Pragmatics and Language Ethics on Students' Communication Skills in Higher Education (Literature Review, Experiment and Replication) - Ikawati, Erna; Lubis , Anita Angraini (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study examines the role of pragmatics and language ethics in student communication in the campus environment, both in academic and social contexts. The purpose of this study is to understand the application of pragmatic principles in student communication, as well as to examine how language ethics affect their interactions in the classroom, on social media, and in everyday social interactions. The method used is a mixed-methods approach, with a narrative literature review technique by reviewing articles relevant to this topic. This was followed by the implementation of a module that replicated the problem strategy. The results of the study indicate that: First, pragmatic principles such as appropriateness of speech, politeness, and communication strategies have a major influence on increasing the effectiveness and ethics of student language. Language ethics, which includes the use of verbal and nonverbal strategies, has been shown to be an important element in fostering polite communication and maintaining interpersonal relationships. Secondly, experimental results on the use of the previously developed module showed a significance of 2.76 from being categorized as sufficient (: 4.86) to good (: 7.62). This significant result contributes to the development of theories of pragmatics and language ethics in education.